Communication is key: a study of the development of communication key skills in China. (10th April 2015) - Harris, Ann; Hua, Zhong
Abstract Different countries offer alternative curricula around what might be designated language, literacy and/or communication. This article focuses on the latter, which has typically been associated with vocational education and often labelled a 'key' or 'core' skill that forms part of a wider set of life and employability skills. In recent years, as China has emerged as a global economy, education has been significant in its policy and development. This research explores staff and student responses to the introduction of a key skills communication course in three Chinese further education vocational colleges. The initiative was prompted by research in China which had suggested that communication is important not just for education (Ye and Li 2007) but also for employability, and that the ability to communicate effectively could be instrumental in individuals' success and development (Tong and Zhong 2008). It explores what communication key skills might mean in a Chinese context and questions notions of transferability and of competence and performance in communication. It analyses how motivation could affect learner success and the relationship of pedagogy to curriculum, and, finally, it considers how communication might be an element in the longer‐term social and political development of critical literacies.